Integrated Manufacturing and Job Design: Moderating Effects of Organizational Inertia - Dean, James W.; Snell, Scott A. (Academy of Management Journal, 1991)
This study investigated the relationship between integrated manufacturing, a new manufacturing paradigm comprising advanced technology, just-in-time inventory control, and total quality management, and job characteristics (task uncertainty and interdependence). We hypothesized that performance, size, and external control would moderate this relationship. Data from plant and functional managers and nonmanagerial employees in 123 companies showed no main effects of integrated manufacturing on job design among employees in operations, quality control and assurance, and production control. Rather, the relationships were contingent on organizational context. We discuss organizational inertia and resource availability as alternative theoretical perspectives on the impact of organizational context.